2021
DOI: 10.1212/nxi.0000000000000951
|View full text |Cite
|
Sign up to set email alerts
|

Altered CSF Albumin Quotient Links Peripheral Inflammation and Brain Damage in MS

Abstract: ObjectiveCNS damage can increase the susceptibility of the blood-brain barrier (BBB) to changes induced by systemic inflammation. The aim of this study is to better understand BBB permeability in patients with MS and to examine whether compromised BBB integrity in some of these patients is associated with CNS damage and systemic inflammation.MethodsRoutine CSF measurements of 121 patients with MS were analyzed including number and type of infiltrating cells, total protein, lactate, and oligoclonal bands, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…Interestingly, we observed that the presence of monocytes/macrophages was associated with conversion to CDMS. This underlines findings on Chitinase 3like 1 (CHI3L1), a glycoprotein secreted by macrophages (41), which was determined as a biomarker in MS (42)(43)(44) and which was also associated with the conversion from CIS to CDMS (45).…”
Section: Discussionsupporting
confidence: 76%
“…Interestingly, we observed that the presence of monocytes/macrophages was associated with conversion to CDMS. This underlines findings on Chitinase 3like 1 (CHI3L1), a glycoprotein secreted by macrophages (41), which was determined as a biomarker in MS (42)(43)(44) and which was also associated with the conversion from CIS to CDMS (45).…”
Section: Discussionsupporting
confidence: 76%
“…Albumin quotients and CSF-specific oligoclonal bands were analyzed as previously reported. 20 Intrathecal Ig synthesis (Ig[loc]) was calculated according to Reiber. 21 …”
Section: Methodsmentioning
confidence: 99%
“…Ex vivo immunophenotyping of intrathecal and paired circulating lymphocytes was performed as previously reported 20 , 22 in a subcohort of 66 patients with MS (eTable 1, links.lww.com/NXI/A590 ). We added SPHERO AccuCount Particles (Spherotech, Inc., Lake Forest, IL) to count absolute numbers following the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 , 5 , 7 , 28 Acute BBB disruption (CSF/serum albumin quotient) in patients with MS is known to correlate with CNS inflammation injury and was recently linked to increased intrathecal neurofilament light chain, chitinase 3-like 1, metalloproteinase 2, and interleukin-6 levels. 29 , 30 However, although levels of fibrinogen in CSF correlate with levels of acute (or past) BBB dysfunction, they do not necessarily reflect the extent of fibrinogenic pathway activation, e.g., processing of fibrinogen into fibrin, which effectively exerts proinflammatory effects. 5 By contrast, D-dimer in CSF is not only a substrate passing the BBB but also a product of the coagulation cascade.…”
Section: Discussionmentioning
confidence: 99%